BENTUK PENERAPAN BUDAYA LITERASI BAGI CALON GURU SEKOLAH DASAR DI UNIVERSITAS KATOLIK MUSI CHARITAS PALEMBANG - Priyanti, Maria Angelina; Triwidayati, Katarina Retno (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2018)
Literacy culture is associated with reading and writing skills. To foster a culture of literacy, prospective elementary school teachers need to have a culture of literacy first. This study aims to describe the method used by lecturers in developing literacy culture for prospective elementary school teachers at Catholic University of Musi Charitas Palembang. This research is a descriptive qualitative study. The results showed that prospective primary school teachers at the Catholic University of Musi Charitas Palembang were given the opportunity to obtain information from various sources. PGSD lecturers provide a real example in literacy culture with the habit of reading and writing. In addition, learning activities are implemented with a model of discussion and assignment in the form of paper writing also facilitating the need to obtain information from various sources through reading and writing activities. The things stated above become a strategy for developing literacy culture for prospective elementary school teachers carried out by UKMC PGSD lecturers